Final survival results from the PENELOPE-B trial investigating palbociclib versus placebo for patients with high-risk HR+/HER2-breast cancer and residual disease after neoadjuvant chemotherapy: brief trial updates - Loibl, Sibylle; Martin, M.; Bonnefoi, H.; Untch, M.; Kim, S. -B.; Bear, H. D.; García-Sáenz, J. A.; Melé Olivé, M.; Mc Carthy, N.; Gelmon, K.; Kelly, C. M.; Im, S. -A.; et al. (Annals of oncology, 2025)
Background - The addition of 1 year of palbociclib to endocrine therapy (ET) did not improve invasive disease-free survival (iDFS) compared with placebo in the PENELOPE-B trial. In this article we report the final survival results of the PENELOPE-B trial. - Patients and methods - The PENELOPE-B trial investigated whether adding 1 year of palbociclib to ET in hormone receptor-positive (HR-positive), human epidermal growth factor receptor 2-negative (HER2-negative) breast cancer (BC) patients with residual disease and high relapse risk (clinical and pathological stage + estrogen receptor status and histological grade score ≥3 or 2 and ypN+) after taxane-based neoadjuvant chemotherapy would improve patient survival. Patients (n = 1250) were randomly assigned to receive either palbociclib 125 mg or placebo d1-21 q4w for 13 cycles in addition to ET. - Results - After a median follow-up of 77.8 months, we recorded 225 deaths (108 palbociclib; 117 placebo) with a 6-year overall survival (OS) rate of 82.4% in the palbociclib arm versus 80.3% in the placebo arm (hazard ratio 0.87, 95% confidence interval (CI) 0.67-1.14, P = 0.31). No significant improvement was noted for palbociclib versus placebo for iDFS, distant disease-free survival or locoregional relapse rate, even with longer follow-up. Upon stratified analysis, we found no benefits across major subgroups. However, exploratory post hoc analyses of the lobular BC (LBC) subgroup indicated a trend toward better survival outcomes in favor of palbociclib (hazard ratio 0.45, 95% CI 0.19-1.07, P = 0.062 for OS and hazard ratio 0.52, 95% CI 0.28-0.97, P = 0.035 for iDFS). - Conclusion - The study concluded that palbociclib did not significantly improve survival outcomes in the overall population. Exploratory post hoc analyses suggested a trend toward better iDFS outcome in patients with LBC receiving palbociclib.